An Inception Cohort Study Assessing the Role of Pneumococcal and other Bacterial Pathogens in Children with Influenza and ILI and a Clinical Decision Model for Stringent Antibiotic Use. Issue 5 (July 2016) - Tief, Franziska; Hoppe, Christian; Seeber, Lea; Obermeier, Patrick; Chen, Xi; Karsch, Katharina; Mühlhans, Susann; Adamou, Eleni; Conrad, Tim; Beresniak, Ariel; Schweiger, Brunhilde; Adam, Thomas; et al.
Background: Influenza-like illness (ILI) is a common reason for paediatric consultations. Viral causes predominate, but antibiotics are used frequently. With regard to influenza, pneumococcal coinfections are considered major contributors to morbidity/mortality. Methods: In the context of a perennial quality management (QM) programme at the Charité Departments of Paediatrics and Microbiology in collaboration with the Robert Koch Institute, children aged 0–18 years presenting with signs and symptoms of ILI were followed from the time of initial presentation until hospital discharge (Charité Influenza-Like Disease = ChILD Cohort). An independent QM team performed highly standardized clinical assessments using a disease severity score based on World Health Organization criteria for uncomplicated and complicated/progressive disease. Nasopharyngeal and pharyngeal samples were collected for viral reverse transcription polymerase chain reaction and bacterial culture/sensitivity and MaldiTOF analyses. The term 'detection' was used to denote any evidence of viral or bacterial pathogens in the (naso)pharyngeal cavity. With the ChILD Cohort data collected, a standard operating procedure (SOP) was created as a model system to reduce the inappropriate use of antibiotics in children with ILI. Monte Carlo simulations were performed to assess cost-effectiveness. Results: Among 2, 569 ChILD Cohort patients enrolled from 12/2010 to 04/2013 (55% male, mean age 3.2 years, range 0–18, 19% >5 years), 411 patients showed laboratory-confirmed influenza, with bacterial co-detection in 35%. Influenza and pneumococcus were detected simultaneously in 12/2, 569 patients, with disease severity clearly below average. Pneumococcal vaccination rates were close to 90%. Nonetheless, every fifth patient was already on antibiotics upon presentation; new antibiotic prescriptions were issued in an additional 20%. Simulation of the model SOP in the same dataset revealed that the proposed decision model could have reduced the inappropriate use of antibiotics significantly ( P ≤0.01) with an incremental cost-effectiveness ratio of -99.55€. Conclusions: Physicians should be made aware that in times of pneumococcal vaccination the prevalence and severity of influenza infections complicated by pneumococci may decline. Microbiological testing in combination with standardized disease severity assessments and review of vaccination records could be cost-effective, as well as promoting stringent use of antibiotics and a personalized approach to managing children with ILI.